Molecular detection and characterization of Hop stunt viroid sequence variants from naturally infected pomegranate (Punica granatum L.) in Tunisia - GORSANE, Faten; ELLEUCH, Amine; HAMDI, Imène; SALHI-HANNACHI, Amel; FAKHFAKH, Hatem (Phytopathologia Mediterranea, 2010)
Tunisian pomegranate Hop stunt viroid (HSVd) variants are described. Dot-blot hybridization, S-Page, and reverse transcription polymerase chain reaction (RT-PCR) of RNA extracts from infected tissues were carried out. Results obtained by these techniques were confirmed by cDNA sequencing. The genetic diversity among the Tunisian variants was investigated, which also involved analysis of sequences of previously described HSVd variants from Tunisian citrus var. clementine and fig, and from fruit trees from other Mediterranean countries. Phylogenetic analysis showed that Tunisian pomegranate HSVd variants were clustered into two groups: a cachexia strain within the citrus type group and a recombinant citrus-plum type group. Results also showed a high haplotype diversity which was not related either to the host or to the geographical origin. Selective neutrality and genetic network tests suggest that the HSVd isolates have spread rapidly.